Healthy Communication Partners Modify Their Speech When Conversing With Individuals With Parkinson's Disease. - Lubold, Nichola; Willi, Megan M.; Borrie, Stephanie A.; Barrett, Tyson S.; Berisha, Visar (Journal of Speech, Language & Hearing Research, 2021)
Purpose: For individuals with Parkinson's disease (PD), conversational interactions can be challenging. Efforts to improve the success of these interactions have largely fallen on the individual with PD. Successful communication, however, involves contributions from both the individual with PD and their communication partner. The current study examines whether healthy communication partners naturally engage in different acoustic-prosodic behavior (speech compensations) when conversing with an individual with PD and, further, whether such behavior aids communication success. Method: Measures of articulatory precision, speaking rate, and pitch variability were extracted from the speech of healthy speakers engaged in goal-directed dialogue with other healthy speakers (healthy-healthy dyads) and with individuals with PD (healthy-PD dyads). Speech compensations, operationally defined as significant differences in healthy speakers' acoustic-prosodic behavior in healthy-healthy dyads versus healthy-PD dyads, were calculated for the three speech behaviors. Finally, the relationships between speech behaviors and an objective measure of communicative efficiency were examined. Results: Healthy speakers engaged in speech characterized by greater articulatory precision and slower speaking rate when conversing with individuals with PD relative to conversations with other healthy individuals. However, these adaptive speech compensations were not predictive of communicative efficiency. Conclusions: Evidence that healthy speakers naturally engage in speech compensations when conversing with individuals with PD is novel, yet consistent with findings from studies with other populations in which conversation can be challenging. In the case of PD, these compensatory behaviors did not support communication outcomes. While preliminary in nature, the results raise important questions regarding the speech behavior of healthy communication partners and provide directions for future work.